Immunological Outcomes Mediated Upon Binding of Heat Shock Proteins to Scavenger Receptors SCARF1 and LOX-1, and Endocytosis by Mononuclear Phagocytes - Murshid, Ayesha; Borges, Thiago J.; Bonorino, Cristina; Lang, Benjamin J.; Calderwood, Stuart K. (Frontiers in Immunology, 2020)
Heat shock proteins (HSP) are a highly abundant class of molecular chaperones that can be released into the extracellular milieu and influence the immune response. HSP release can occur when cells undergo necrosis and exude their contents. However, HSPs are also secreted from intact cells, either in free form or in lipid vesicles including exosomes to react with receptors on adjacent cells. Target cells are able recognize extracellular HSPs through cell surface receptors. These include scavenger receptors (SR) such as class E member oxidized low-density lipoprotein receptor-1 (LOX-1, aka OLR1, Clec8A and SR-E1) and scavenger receptor class F member 1 (SCARF1, aka SREC1). Both receptors are expressed by dendritic cells (DC) and macrophages. These receptors can bind HSPs coupled to client binding proteins and deliver the chaperone substrate to the pathways of antigen processing in cells. SR are able to facilitate the delivery of client proteins to the proteasome, leading to antigen processing and presentation, and stimulation of adaptive immunity. HSPs may also may be involved in innate immunity through activation of inflammatory signaling pathways in a mechanism dependent on SR and toll-like receptor 4 (TLR4) on DC and macrophages. We will discuss the pathways by which HSPs can facilitate uptake of protein antigens and the receptors that regulate the ensuing immune response.